Labelizing of Manufacturing Halal Industry Products for Achieving Consumer Satisfaction In The Perspective of Maslahah Daruriyah - Kadir, Syahruddin (El-Qish: Journal of Islamic Economics, 2022)
Maslahah are all forms of goodness with worldly and hereafter dimensions that bring goodness in all aspects that do not cause harm in production, distribution and consumption activities. The labeling of halal products in the manufacturing industry from the perspective of maslahah daruriyah focuses on halal guarantees, consumer protection is marked by halal symbol on the packaging. The purpose of this study was to determine the categorization of maslahah daruriyah on the labeling of halal products and consumption satisfaction with the labeling of halal products. The method is descriptive qualitative. The results of the study prove that the labeling of halal products is categorized as maslahah daruriyah which of course the obligation of halal labeling is carried out in stages because its existence is needed by human life for the benefit of maintaining religion, soul, mind, lineage and property. Consumption satisfaction known as maslahah with the understanding that the needs are fulfilled both physically and spiritually. Islam attaches great importance to physical and non-physical balance based on sharia values